Characteristics of An Effective EFL Teacher in Indonesia: Expectations and Realities in A Technology-Enhanced Flipped Classroom - Arif Husein Lubis; Didin Samsudin (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2021)
Previous literature has articulated the contributing role of personality more than teaching competence to be an effective EFL teacher. However, the ideal qualities of an effective EFL teacher in a technology-enhanced flipped English classroom are not much revealed. This paper seeks to compare the ideal teacher’s attitudes and teaching styles with the teacher’s actual practices in a technology-enhanced flipped English classroom from the students’ perceptions. Eighty-three Indonesian undergraduate EFL students majoring in information technology participated in this research. A questionnaire with a checklist and open-ended items was filled out after the students accomplished a 16-week English course. The results showed that an effective EFL teacher in a technology-enhanced flipped English classroom should possess and exemplify the attitudes of patience, friendliness, and niceness, as perceived by the students. Most students also envisaged that an effective EFL teacher in such a learning context can use various, innovative, easy-to-follow methods and employ English and Indonesian alternately. The realities generally accorded with the students’ expectations. More students favored the use of various kinds of instructional technology by the teacher. However, the teacher was less favored for being too serious, not being open to students, giving unclear instructions for doing the assignments, and giving less guidance to use the educational technology